5x+x-2=5x+6

Simple and best practice solution for 5x+x-2=5x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+x-2=5x+6 equation:


Simplifying
5x + x + -2 = 5x + 6

Reorder the terms:
-2 + 5x + x = 5x + 6

Combine like terms: 5x + x = 6x
-2 + 6x = 5x + 6

Reorder the terms:
-2 + 6x = 6 + 5x

Solving
-2 + 6x = 6 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-2 + 6x + -5x = 6 + 5x + -5x

Combine like terms: 6x + -5x = 1x
-2 + 1x = 6 + 5x + -5x

Combine like terms: 5x + -5x = 0
-2 + 1x = 6 + 0
-2 + 1x = 6

Add '2' to each side of the equation.
-2 + 2 + 1x = 6 + 2

Combine like terms: -2 + 2 = 0
0 + 1x = 6 + 2
1x = 6 + 2

Combine like terms: 6 + 2 = 8
1x = 8

Divide each side by '1'.
x = 8

Simplifying
x = 8

See similar equations:

| 15y+3(2-y)=-24 | | (3k-4)(3k+4)= | | 2*.5+2Y=15 | | 7+7-3+70+1= | | e-4.7=2.9 | | 2+.5+2Y=15 | | 0.5(p+3)=3(0.1+0.6p) | | -2k+5k-9+2k= | | 4x+10[2x+2]-15= | | 75=15k+6 | | 9x^3-9x^2-x+1=0 | | 10+3[x+5]-x= | | b-339=-77 | | 20-7x=4(2x-6) | | 6x-1=-4 | | 9x^2-18x-91=0 | | 3x^2+28x-9=0 | | -6x+4=-10x+24 | | 2x+2(-6x-4)=15 | | -10x-8=15 | | j-3.9=3.8 | | 1+12x=-21+x | | 14+3x=5x-14 | | 10v+5v= | | 4x+38=11x-37 | | 2(x+7)-8=22 | | x-4=7x+20 | | -6.21+-4.3t=9.8(t+2.1) | | 3x+9y-6y+10x= | | (4y-5)(2y-3)= | | 8x-12+x=9x+8x | | 4x+9=2x-14 |

Equations solver categories